(untitled) (Cambridge, UK,New York, 2002)
This volume comprises articles from three outstanding researchers who work at the cusp of analysis and logic. The emphasis is on active research topics; many results are presented that have not been published before and open problems are formulated. Considerable effort has been made by the authors to make their articles accessible to mathematicians in general and not just to specialists in the areas of research covered.
Keywords: Mathematical analysis,Logic, Symbolic and mathematical,Toán học giải tích,Lôgic, Toán học và ký hiệu